The ambivalent legacy of Dartmouth five decades on: What, now, should we teach the English teachers? - Jones, Jo (AATE, 2017)
© 2017, AATE - Australian Association Teaching English. All rights reserved. This essay expresses a profoundly ambivalent response to the legacy of Dartmouth, particularly Dixon’s ‘Growth’ Model of English. English educators owe a debt to Dixon in terms of innovative pedagogical methods that are part of the daily shapes of tertiary and high school English classes, including the way drama and performance invoke excitement and engagement, and the advantages of energised spoken formats used to debate issues and discuss texts. On the other hand some of Dartmouth’s key conceptual and methodological tenets, as they have played out over the decades, have become counter-productive elements of English teaching in the twenty-first century. Here, a final-year tertiary teacher education course - ‘Teaching, Literature, Culture’ - is used to challenge the dimensions of the Growth Model as they manifest in the present time.